Hematological assessment of gasoline exposure among petrol filling workers in Baghdad - Sahb, Ali A. A. (Journal of the Faculty of Medicine Baghdad, 2012)
Background: Petrol station attendants are workers chronically exposed to petroleum derivatives primarily through inhalation of the volatile fraction of petrol during vehicle refueling.The adverse health effects of gasoline exposure may be primarily related to impairment of the haemopoietic system with bone marrow depression.Objective: The evaluation of hematopoietic changes among petrol filling workersMethods: a cross sectional survey was carried out with 292individuals, 146 petrol filling workers who spent their working hours in the stations of petrol filling in Baghdad city-group (1) and 146 individuals from people who already work in station as overseers - group (2), were investigated for the effect of gasoline polluted air which arise from inhalation or absorption of benzene through skinResult: Of examined 292individuals, 146 petrol filling workers (all of them) were found with hematopoietic changes. out of 6 potential risk factors, only one (smoking habit)found to be significantly associated with the presence of white blood cell changes(p